2018
DOI: 10.1016/j.amepre.2018.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Screening and Counseling in the U.S.: Smokers With Mental Health and Substance Use Problems

Abstract: Like smokers with mental health problems, smokers with only substance use problems are at increased risk of tobacco-related morbidity and mortality. Yet, unlike smokers with mental health problems, their rates of tobacco screening and cessation counseling by general medical providers do not reflect this elevated risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Tobacco disparity groups, including those suffering from mental illnesses and substance use disorders, utilize tobacco products at a disproportionate rate and face greater tobacco-related morbidity as a result [ 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The disproportionate use of tobacco can effectively be addressed by increasing the occurrence of tobacco screenings, a cost-effective method for improving patient outcomes in settings where patients with behavioral health disorders receive care [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tobacco disparity groups, including those suffering from mental illnesses and substance use disorders, utilize tobacco products at a disproportionate rate and face greater tobacco-related morbidity as a result [ 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The disproportionate use of tobacco can effectively be addressed by increasing the occurrence of tobacco screenings, a cost-effective method for improving patient outcomes in settings where patients with behavioral health disorders receive care [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that individuals in this category face greater tobacco-related morbidity from their elevated tobacco use, cited as about two to four times greater than the general US population. As a result, individuals with behavioral health needs are a tobacco-related health disparity group despite not being ubiquitously recognized as one [ 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Thus, there is a dire need to address tobacco use among behavioral health patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional study on Tobacco Screening and Counselling among smokers in the United States of America has shown different polar among active smokers' behaviour in seeking health screening (15). This study revealed that smokers with mental health problems tended to attend tobacco screening and cessation programs compared to smokers without mental health problems and substance use.…”
Section: Smokers' Health-seeking Behaviourmentioning
confidence: 78%